Analisis Kualitas Pelayanan Terhadap Loyalitas Pelanggan pada PT. JKS Realty Bandung - Sandra Virky Ramadhani; Chandra Hendriyani (Akademi Sekretari Manajemen Taruna Bakti, 2022)
Service quality is one of the important factors that the company provides to customers to meet customer needs and make customers loyal to the company. The purpose of this study was to determine the quality of service on customer loyalty at PT JKS Realty Bandung. PT JKS Realty provides four-star hotel-class apartment facilities that are fast in responding to problems faced by customers and create customer loyalty programs through cashback programs, co-branding, discounts, and privilege programs so that loyal customers can be seen from repeat purchases from repeat customers. have more than 1 unit of which 96 people. Loyalty will provide more benefits for the company's business continuity because the customer has experienced one of the products or services of the company. The research method uses descriptive qualitative methods with data collection techniques through observation and secondary data. The results of this study indicate the existence of customer loyalty to the company because the quality of service provided by the company meets customer needs.